Reduction of VEGF Levels by Phaleria macrocarpa Flavonoids in an Endometriosis Mouse (Mus musculus) Model - Amina Diarsy; Fany Hardiati Amalia; Sutrisno Sutrisno; Tatit Nurseta; Safrina Dewi Ratnaningrum (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Endometriosis occurs when endometrial-like cells proliferate at ectopic sites outside the uterus. The advancement of endometriotic lesions is strongly influenced by VEGF, as it stimulates the formation of new blood vessels. In contrast, flavonoids derived from Phaleria macrocarpa extract possess inhibitory effects on both pro-inflammatory signaling molecules and pro-angiogenic pathways. This study investigated the effects of flavonoids from Phaleria macrocarpa extract on VEGF levels in the peritoneal fluid of endometriosis mouse models. This research employed a post-test-only control group experimental design. A total of thirty mice (Mus musculus) were assigned to six groups: a healthy control group, an untreated endometriosis group, and four endometriosis groups receiving isolated flavonoids from Phaleria macrocarpa extract at doses of 3.75, 7.5, 15, and 30 mg/mouse/day (n=5). Peritoneal fluid samples were collected from all groups to examine VEGF levels using ELISA. The results were expressed as mean ± SD and subsequently evaluated using a one-way ANOVA with LSD post-hoc test at a significance level of p-value < 0.05. Flavonoids at the dose of 30 mg/day significantly decreased the VEGF levels compared to the group of endometriosis mouse models (p-value=0.001). Flavonoids decreased VEGF levels as an angiogenic factor in peritoneal fluid, which may play a role in the proliferation of endometriosis tissue. Keywords: Flavonoid, Phaleria macrocarpa, VEGF, Endometriosis